Communication Ethics in Football Fan Interactions with Blackpink's K-pop Fandom: Etika Komunikasi dalam Interaksi antara Penggemar Sepak Bola dengan Fandom K-Pop Blackpink - Anggraeni, Nur Halimah; Adiprabowo, Vani Dias (Universitas Darussalam Gontor collaboration with ISKI (Ikatan Sarjana Ilmu Komunikasi Indo, 2023)
Communication between humans can be established more easily and quickly with the development of advanced technology today. The number of social media that exists at this time, makes the communication process can be done easily. Currently, the communication process has become easier so that we know media communication, namely in this study through Instagram social media. In using social media there are communication ethics that must be considered, so it should not be arbitrary in communicating. This study examined the media behavior of football fans on Blackpink's K-pop fandom on Blackpink's Instagram social media account. The research method in this study uses a qualitative approach. Data collection is carried out by observing a case that is happening through Instagram social media. The data collection method used is by observing and analyzing the ethics in communicating football fans with Blackpink's K-pop fandom on Instagram media through comments shown on the blackpinkofficial Instagram account. The results of this study, we can see that the communication we use on Instagram, over time can reduce the rules contained in it. The reason is, social media is a gathering place for various kinds of human nature, both mature in addressing problems and those who are still childish, causing poor communication ethics of football fans and Blackpink fans.